Global Burden of Head and Neck Cancer: Economic Consequences, Health, and the Role of Surgery. (March 2020) - Patterson, Rolvix H.; Fischman, Victoria G.; Wasserman, Isaac; Siu, Jennifer; Shrime, Mark G.; Fagan, Johannes J.; Koch, Wayne; Alkire, Blake C.
Objective: We aimed to describe the mortality burden and macroeconomic effects of head and neck cancer as well as delineate the role of surgical workforce in improving head and neck cancer outcomes. Study Design: Statistical and economic analysis. Setting: Research group. Subjects and Methods: We conducted a statistical analysis on data from the World Development Indicators and the 2016 Global Burden of Disease study to describe the relationship between surgical workforce and global head and neck cancer mortality-to-incidence ratios. A value of lost output model was used to project the global macroeconomic effects of head and neck cancer. Results: Significant differences in mortality-to-incidence ratios existed between Global Burden of Disease study superregions. An increase of surgical, anesthetic, and obstetric provider density by 10% significantly correlated with a reduction of 0.76% in mortality-to-incidence ratio ( P < .0001; adjusted R 2 = 0.84). There will be a projected global cumulative loss of $535 billion US dollars (USD) in economic output due to head and neck cancer between 2018 and 2030. Southeast Asia, East Asia, and Oceania will suffer the greatest gross domestic product (GDP) losses at $180 billion USD, and South Asia will lose $133 billion USD. Conclusion: The mortality burden of head and neck cancer is increasing and disproportionately affects those in low- and middle-income countries and regions with limited surgical workforces. This imbalance results in large and growing economic losses in countries that already face significant resource constraints. Urgent investment in the surgical workforce is necessary to ensure access to timely surgical services and reverse these negative trends.